Pharmacokinetics and Pharmacodynamics of Recombinant Human Angiotensin-Converting Enzyme 2 in Healthy Human Subjects - Haschke, Manuel; Schuster, Manfred; Poglitsch, Marko; Loibner, Hans; Salzberg, Marc; Bruggisser, Marcel; Penninger, Joseph; Krähenbühl, Stephan (Clinical pharmacokinetics, 2013)
Background and Objectives Angiotensin-converting enzyme 2 (ACE2) converts angiotensin II (Ang1-8) to angiotensin 1-7 (Ang1-7), a functional antagonist of Ang1-8, with vasodilatory, antiproliferative, antiangiogenic, and anti-inflammatory properties. In conditions with an unbalanced renin–angiotensin–aldosterone system with elevated Ang1-8, administration of ACE2 has shown promising effects in a variety of animal models. Enhancing ACE2 activity by exogenous administration of ACE2 might also be beneficial in human diseases with pathologically elevated Ang1-8. As a first step we performed a first-in-man study to determine pharmacokinetics, pharmacodynamics, safety, and tolerability of recombinant ACE2 in healthy volunteers. Methods Recombinant human ACE2 (rhACE2) was administered intravenously to healthy human subjects in a randomized, double-blind, placebo-controlled, single-dose, dose-escalation study followed by an open-label multiple-dose study. ACE2 concentrations were determined by quantifying ACE2 activity and ACE2 content in plasma samples. Concentrations of the angiotensin system effector peptides Ang1-8, Ang1-7, and Ang1-5 were determined using a liquid chromatography–tandem mass spectrometry method. Results Single rhACE2 doses of 100–1,200 μg/kg caused a dose-dependent increase of systemic exposure with biphasic elimination and a dose-independent terminal half-life of 10 h. In all single-dose cohorts, Ang1-8 decreased within 30 min postinfusion, angiotensin 1-7 (Ang1-7) either increased (100 and 200 μg/kg doses), decreased, or remained unchanged (400–1,200 μg/kg doses), whereas angiotensin 1-5 (Ang1-5) transiently increased for all doses investigated. With the exception of the lowest rhACE2 dose, the decrease in Ang1-8 levels lasted for at least 24 h. Repeated dosing (400 μg/kg for 3 or 6 days) caused only minimal accumulation of ACE2, and Ang1-8 levels were suppressed over the whole application period. Conclusions Administration of rhACE2 was well tolerated by healthy human subjects. Exposure was dose dependent with a dose-independent terminal elimination half-life in the range of 10 h. Despite marked changes in angiotensin system peptide concentrations, cardiovascular effects were absent, suggesting the presence of effective compensatory mechanisms in healthy volunteers.